2002
DOI: 10.1345/aph.1a144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Colesevelam on Lovastatin Pharmacokinetics

Abstract: Colesevelam had no significant effect on lovastatin pharmacokinetics when coadministered with lovastatin at dinner. A split-dosing regimen resulted in alterations in pharmacokinetic parameters for lovastatin and lovastatin hydroxyacid that are likely due to known differences in the pharmacokinetics of lovastatin when administered to patients with meals or in a fasting state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…[40][41][42] No significant interaction has been shown during colesevelam and fenofibrate co-administration or after a 4-hour dosing interval. 43 Although studies have not evaluated any interaction between colesevelam and ezetimibe, significant further reduction in LDL-c levels occurs with combined colesevelamezetimibe therapy.…”
Section: Drug-drug Interactionmentioning
confidence: 97%
“…[40][41][42] No significant interaction has been shown during colesevelam and fenofibrate co-administration or after a 4-hour dosing interval. 43 Although studies have not evaluated any interaction between colesevelam and ezetimibe, significant further reduction in LDL-c levels occurs with combined colesevelamezetimibe therapy.…”
Section: Drug-drug Interactionmentioning
confidence: 97%
“…Colesevelam has a synergistic effect in lowering LDL when used in conjunction with statins [10], which offers further treatment options for patients who are on maximum doses of statins and have not achieved target LDL levels. Importantly, colesevelam does not affect the pharmacokinetics or absorption of statins, so the two drugs can be used in combination without adjusting the schedule or dosing of the statin [11]. Combination studies with colesevelam and modest doses of simvastatin have demonstrated a 40% reduction in LDL cholesterol levels with a concomitant decrease in apoB-100 being greater than with either colesevelam or simvastatin alone [12•].…”
Section: Colesevelammentioning
confidence: 99%
“…The literature has reported drug-drug interactions between lovastatin and drugs or related products with effect on drugs such as colesevelam, gemfibrozil, itraconazole or dietary supplements determined via pharmacokinetic studies [10][11][12][13][14][15]. Berberine is an alkaloid available from the medicinal plant Coptis chinensis that is widely used clinically in the treatment of gastrointestinal infections, diabetes, hypertension, and hypercholesterolemia.…”
Section: Introductionmentioning
confidence: 99%
“…In the in vitro HepG2 cells experiments, berberine could increase the metabolic activity by increasing the metabolic parameters of CL, which was increased from 1.06 to 1.48 mL/10 5 (cell)·h −1 with the induction of berberine, the Km was increased three times in berberine induced group as well, which was compliance with the obtained pharmacokinetics parameter from AUC0-12 of lovastatin decreased 2.5 times (approximately three times). The literature has reported drug-drug interactions between lovastatin and drugs or related products with effect on drugs such as colesevelam, gemfibrozil, itraconazole or dietary supplements determined via pharmacokinetic studies [10][11][12][13][14][15]. Berberine is an alkaloid available from the medicinal plant Coptis chinensis that is widely used clinically in the treatment of gastrointestinal infections, diabetes, hypertension, and hypercholesterolemia.…”
Section: Introductionmentioning
confidence: 99%